Nodular tertiary syphilis in an immunocompetent patient - Maraya de Jesus Semblano Bittencourt; Arival Cardoso de Brito; Bianca Angelina Macêdodo Nascimento; Alessandra Haber Carvalho; Marion Guimarães Drago (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Acquired syphilis can be divided into primary, secondary, latent, and tertiary stages. About 25% of patients with untreated primary syphilis will develop late signs that generally occur after three to five years, with involvement of several organs. The authors present an immunocompetent female who developed a tertiary stage syphilis presenting with long-standing nodular plaques.